Insights Into the Mineralogy and Surface Chemistry of Extracellular Biogenic S0 Globules Produced by Chlorobaculum tepidum - Marnocha, Cassandra L.; Sabanayagam, Chandran R.; Modla, Shannon; Powell, Deborah H.; Henri, Pauline A.; Steele, Andrew S.; Hanson, Thomas E.; Webb, Samuel M.; Chan, Clara S. (Frontiers in Microbiology, 2019)
Elemental sulfur (S0) is produced and degraded by a diverse group of microorganisms. For Chlorobaculum tepidum, an anoxygenic phototroph, sulfide is oxidized to produce extracellular S0 globules, which can be further oxidized to sulfate. While some sulfur-oxidizing bacteria (e.g. Al. vinosum) are also capable of growth on commercial S0 as an electron donor, Cba. tepidum is not. Even colloidal sulfur sols, which appear indistinguishable from biogenic globules, do not support the growth of Cba. tepidum. Here, we investigate the properties that make biogenic S0 globules special and distinct from abiotic forms of S0. We found that S0 globules produced by Cba. tepidum and abiotic S0 sols are quite similar in terms of mineralogy and material properties, but the two are distinguished primarily by the properties of their surfaces. Cba. tepidum’s globules are enveloped by a layer of organics (protein and polysaccharides), which results in a surface that is fundamentally different from that of abiotic S0 sols. The organic coating on the globules appears to slow the aging and crystallization of amorphous sulfur, perhaps providing an extended window of time for microbes in the environment to access the more labile forms of sulfur as needed. Overall, our results suggest that the surface of biogenic S0 globules may be key to cell-sulfur interactions and the reactivity of biogenic S0 in the environment.